Green Solid Electrolyte with Cofunctionalized Nanocellulose/Graphene Oxide Interpenetrating Network for Electrochemical Gas Sensors. Issue 11 (25th September 2017) - Zhang, Jing; Jiang, Gaopeng; Goledzinowski, Maciej; Comeau, Felix J. E.; Li, Kecheng; Cumberland, Timothy; Lenos, Jared; Xu, Pan; Li, Matthew; Yu, Aiping; Chen, Zhongwei
Abstract: A cofunctionalized cellulose/graphene oxide (GO) proton‐conducting solid electrolyte with a 3D interpenetrating network structure is developed in an efficient and green strategy, and successfully applied in an electrochemical gas sensor for the detection of alcohol, namely an alcohol fuel‐cell sensor. With grafted sulfonic acid groups onto the surface of cellulose nanofibers and GO nanosheets, the membrane is endowed with proton conductivity along both the through‐plane and the in‐plane ion‐transport channels. The alcohol fuel‐cell sensor equipped with cofunctionalized cellulose/GO membrane demonstrates great responses to ethanol vapor at different concentrations, showing excellent linearity and sensitivity, as well as low ethanol‐detection limits approaching 25 ppm. This novel concept of developing a cofunctionalized cellulose/GO membrane opens a promising route for the application of ion‐conducting solid electrolyte in electrochemical devices, particularly in electrochemical gas sensors. Abstract : A cofunctionalized cellulose‐based proton‐conducting solid electrolyte with graphene oxide modification is demonstrated on an electrochemical gas sensor. Superior in‐plane and through‐plane conductivities, high water content, and sensitive detection to low limits of ethanol vapor demonstrate its promising application in an alcohol fuel‐cell sensor.